Latest updates on the serotonergic system in depression and anxiety - Lin, Jianwen; Liu, Wenxin; Guan, Jing; Cui, Jianing; Shi, Ruolin; Wang, Lu; Chen, Dong; Liu, Yi (Frontiers in Synaptic Neuroscience, 2023)
Psychiatric disorders are amongst the leading causes of global health burden, with depression and anxiety being the most disabling subtypes. The two common disorders, depression and anxiety, usually coexist and are pathologically polygenic with complicated etiologies. Current drug-based therapies include selective serotonin reuptake inhibitors, serotonin and norepinephrine reuptake inhibitors, and 5-hydroxytryptamine partial agonists. However, these modalities share common limitations, such as slow onset and low efficacy, which is why potential mechanistic insights for new drug targets are needed. In this review, we summarize recent advances in the brain localization, pathology, and therapeutic mechanisms of the serotonergic system in depression and anxiety.